Prenatal listening to songs composed for pregnancy and symptoms of anxiety and depression: a pilot study - Chineze Nwebube; Vivette Glover; Lauren Stewart (BMC, 2017)
Abstract Background Prenatal anxiety and depression are distressing for the expectant mother and can have adverse effects on her fetus and subsequently, her child. This study aimed to determine whether listening to specially composed songs would be an effective intervention for reducing symptoms of prenatal anxiety and depression. Methods Pregnant women were recruited online and randomly assigned to one of two groups: the music group (daily listening to specially composed songs) or control group (daily relaxation) for 12 weeks each. Self-report questionnaires were used to assess symptoms of State and Trait anxiety (Spielberger) and depression (Edinburgh Postnatal Depression Scale (EPDS)). Trait anxiety was measured as the primary outcome, while State anxiety and depression were the secondary outcomes. 111 participants were randomised to each group. 20 participants in the intervention group and 16 participants in the active control group completed the study. Results The music group demonstrated lower Trait Anxiety (p = .0001) (effect size 0.80), State Anxiety (p = .02) (effect size 0.64), and EPDS (p = .002) (effect size 0.92) scores at week 12 compared to baseline, by paired t test. There were no such changes in the control group. Conclusions Though this pilot study had high levels of attrition, the results do suggest that regular listening to relaxing music should be explored further as an effective non-pharmacological means for reducing prenatal anxiety and depression. Trial registration ClinicalTrials.gov NCT02776293 LV-001. Registered 17 May 2016. Retrospectively registered.